Clicking on the Truth: Understanding How Samarinda Residents Use Fact-Checking Tools (Open Society Conference, 2025)
This research discusses the practice of using fact-checking tools by the Samarinda City residents in the context of digital literacy. The main purpose of the study is to understand the pattern of use, level of understanding, and attitude of the community towards fact-checking tools, as well as evaluating the extent to which the tool can help overcome hoaxes on social media. This study is academically important because it fills the literature gap on information verification behavior at the city level, as well as practically provides a basis for digital literacy strategies and community education campaigns. This research uses a qualitative approach to gain a deep understanding of the experience, perception, and challenges of residents. Data was collected through the Google Form online questionnaire filled by 114 active respondents of internet users in Samarinda City. The analysis was carried out descriptively and thematically to group answers based on the main themes that emerged. The findings show that the majority of Samarinda City residents rely on social media as a source of information, with a high frequency of hoax exposure. Although some realize the importance of verification of information, knowledge, and use of fact-checking tools is still low, with Cekfakta.com into the most well-known platforms. This study concluded that digital literacy plays a crucial role in increasing community resilience to misinformation, and individual awareness is the main key in combating hoaxes. The practical implications of this study include the need to increase education and socialization about fact-checking tools, as well as the development of digital literacy strategies that are appropriate to the local context to support more active and critical community participation in information verification.